Autoriti Preskriptif Al-Quran Dalam Pembuktian Syariah: Tinjauan Terhadap Pengakuan, Keterangan Saksi Dan Sumpah - Wan Abdul Fattah Wan Ismail; Hasnizam Hashim; Baidar Mohammed Mohammed Hassan; Mualimin Mochammad Sahid; Ahmad Syukran Baharuddin; Mohamad Aniq Aiman Alias; Norma Jusof (Universiti Sains Islam Malaysia, 2026)
Non-Indexed Publication